IFC Annual Report 2012 : Innovation, Influence, Demonstration, Volume 2. Results - International Finance Corporation (Washington, DC: World Bank, 2013)
This annual report of the International Finance Corporation (IFC) summarizes the innovation and leadership roles in the private sector during fiscal year 2012. The IFC invested a record $20.4 billion in 103 developing countries, reflecting a doubling of annual commitments over the last five years. Those investments included nearly $5 billion mobilized from other investors, and an investment for Sub-Saharan Africa totaling $2.7 billion, nearly twice as much as five years ago. The advisory services program expenditures grew to $197 million, up more than 50 percent over the last five years. Advisory services also helped 33 client governments introduce 56 investment-climate reforms that will improve access to basic services for more than 16 million people. IFC investment clients helped support 2.5 million jobs in 2011 and made 23 million loans totaling more than $200 billion to micro, small, and medium enterprises. Net income before grants to the International Development Association (IDA) totaled $1.66 billion. The IFC has invested more than $23 billion in IDA countries, nearly $6 billion of it in fiscal year 2012 alone.